2016
DOI: 10.21273/horttech.26.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Sprays of Flurprimidol, Paclobutrazol, and Uniconazole Suppress Height of Seed-propagated New Guinea Impatiens

Abstract: Our objective was to quantify the efficacy of foliar plant growth retardant applications on plant height and time to flower of seed-propagated new guinea impatiens (Impatiens hawkeri) produced in packs and flats. ‘Divine Cherry Red’, ‘Divine Scarlet Bronze Leaf’, and ‘Divine White Blush’ seedlings were planted in 1801-cell packs. Seven days after planting, deionized water (control) or solutions containing ancymidol (15 to 60 mg·L−1), chlormequat chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
4
9
0
Order By: Relevance
“…Our results on the comparative efficacy of the different active ingredient agree with previous reports (Currey and Erwin, 2012;Currey and Lopez, 2011;Currey et al, 2016). Currey and Erwin (2012) treated 11 different kalanchoe (Kalanchoe) species with a variety of PGRs, including ancymidol, paclobutrazol, and uniconazole.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on the comparative efficacy of the different active ingredient agree with previous reports (Currey and Erwin, 2012;Currey and Lopez, 2011;Currey et al, 2016). Currey and Erwin (2012) treated 11 different kalanchoe (Kalanchoe) species with a variety of PGRs, including ancymidol, paclobutrazol, and uniconazole.…”
Section: Resultssupporting
confidence: 91%
“…Alternatively, paclobutrazol was effective on nine kalanchoe species and uniconazole suppressed stem elongation in every species. Similar variation in the efficacy of PGR active ingredient in controlling growth of new guinea impatiens (Impatiens hawkeri) was reported by Currey et al (2016). Three cultivars of Divine new guinea impatiens were treated with seven PGRs, including ancymidol, flurprimidol, paclobutrazol, and uniconazole.…”
Section: Resultssupporting
confidence: 58%
“…Soil drenches of uniconazole retarded shoot and petiole elongation of Brassaia actinophylla (Wang et al, 1990). In another study flurprimidol, paclobutrazol and uniconazole suppressed height of 'Divine Cherry Red', 'Divine Scarlet Bronze Leaf' and 'Divine White Blush' Impatiens hawker cultivars (Currey et al, 2016). It was reported that paclobutrazol and uniconazole application reduced plant size and stem length of Kalanchoe 'Rako' (Lee et al, 2003).…”
Section: Methodsmentioning
confidence: 98%
“…Increasing paclobutrazol concentration led to suppressed growth of angelonia and petunia across biocontainer types, with growth suppression increasing with concentration (Tables 6 and 7). Research has demonstrated that growth inhibition of containerized ornamental plants increases with increasing concentrations of PGRs up to a species-or cultivar-specific concentration, at which suppression is saturated (Barrett, 1982;Currey et al, 2016b;De Hertogh et al, 1976;Whipker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Triazoles are the most effective class of PGR labeled for use on flowering ornamental plants; growth control of flowering plants can be achieved when using substrate drench concentrations as low as 0.05 mg•L -1 (Currey and Lopez, 2011). Efficacy of PGR applications can be affected by plant genetics (Currey et al, 2016a), active ingredient (Currey et al, 2016b), application method (Hawkins et al, 2015), and, in the case of substrate drenches, substrate components (Barrett, 1982;Bonaminio and Larson, 1978;Currey et al, 2010). Triazole PGRs are readily absorbed by organic substrate components such as sphagnum peat moss (Barrett, 1982), and the addition of organic substrate amendments affects drench efficacy differently.…”
Section: Introductionmentioning
confidence: 99%